Right ventricular dysfunction and pulmonary hypertension following sub‐massive pulmonary embolism. (20th January 2016) - Samaranayake, Chinthaka B.; Royle, Gordon; Jackson, Sharon; Yap, Elaine
Abstract: Background and objectives: Persistent right ventricular dysfunction (RVD) and pulmonary hypertension (PHT) are important outcomes following sub‐massive pulmonary embolism (PE). The aims were to determine the rates and factors associated with RVD and/or PHT on echocardiography (ECHO) and the rate of 30‐day and 1‐year all‐cause mortality following sub‐massive PE. Patients who received thrombolysis and non‐thrombolysis were also compared. Methods: Consecutive patients with sub‐massive PE over a five year period with at least 1‐year follow‐up were retrospectively identified. Regression analysis was performed to identify predictors of outcomes. Results: Eighty‐seven patients met inclusion criteria. Sixty‐one (70%) had admission ECHOs with a follow‐up ECHO in 42 (48.3%) at a mean of 7.6 months (SD 5.2). Fifty‐one had RVD (58.6%) and 35 (40.2%) had PHT on admission. The rates of persistent RVD and raised right ventricular systolic pressure in this study population were 12% and 17%, respectively. Thrombolysis was associated with a trend towards improvement of PHT (53.3% PHT on admission to 0% PHT on follow‐up in the thrombolysis group, P  = 0.29). The rate of 30‐day and 1‐year all‐cause mortality were 12.6% and 21.8%, respectively. Thirty‐day all‐cause mortality was independently predicted by the presence of right heart strain on computed tomography pulmonary angiography [OR 3.7 ( P  = 0.045)], echocardiographic evidence of RVD [OR 3.9 ( P  = 0.041)] and age. Conclusion: The majority of patients with RVD and PHT at the time of sub‐massive PE improve on follow‐up; however, there is a subset who remain abnormal. Future studies are needed to identify modifiable risk factors for these complications.